Structure and beating behavior of the sperm motility apparatus in aquatic animals - Bondarenko, Volodymyr; Cosson, Jacky (Theriogenology, 2019)
Motility is a characteristic function of the male gamete, which allows spermatozoa to actively reach and penetrate the female gamete in organisms with internal and external fertilization. Sperm motility is acquired under the control of many extrinsic and intrinsic factors and is based on a specialized structure of the sperm flagellum called "axoneme". An overview of how the sperm flagellum is organized, and it operates to support cell motility is presented, with special focus on the molecular mechanisms and factors involved in the development, maintenance and control of motility. Data obtained in aquatic organisms with external fertilization, such as sea urchins, ascidians or fishes are critically analyzed because they constitute model species on which most of the present day understanding of sperm motility function is based. In most animal species, sperm motility is dependent on a long appendage called flagellum. Flagella are essential organelles found in most eukaryotic cells; their basic structure is the axoneme, which consists of a scaffold of microtubules and is responsible for movement in an autonomous manner if ATP-energy is present. Flagellar beat propels the cell through the medium which surrounds sperm cells and is responsible of the translational drive of spermatozoa. The present paper includes: (1) an introduction to typical sperm morphology and ultrastructure in most aquatic species, (2) the motility apparatus or axoneme of the spermatozoa: the axoneme, (3) the structural and biochemical composition of the axoneme, (4) the axonemal motor or dynein, and its operation, (5) the regulation of motility at axoneme and cell membrane levels, including several effectors such as Ca2+ ions, (6) biophysical features of the wave propagation mechanism in motile spermatozoa, (7) the energy production and consumption, and (8) the building of a flagellum. Flagellar beating in aquatic animals is illustrated using several examples in figures and video-clips. These types of data are also used for computer simulation of various aspects of the modulation of sperm motility of marine animals.
Keywords: Sperm Motility; bezobratlí; Flagella; mužské pohlaví; Ions; Aquatic Organisms; flagella; Invertebrates; obratlovci; zvířata; Regulation; Vertebrates; Flagellum; vodní organismy; Sea urchin; Species Specificity; motilita spermií; Osmolarity; druhová specificita; Spermatozoa; spermie; Male; Animals